Adalimumab dose escalation is effective and well tolerated in Crohn's disease patients with secondary loss of response to adalimumab. Issue 2 (February 2017) - Duveau, Nicolas; Nachury, Maria; Gerard, Romain; Branche, Julien; Maunoury, Vincent; Boualit, Medina; Wils, Pauline; Desreumaux, Pierre; Pariente, Benjamin
Abstract: Background: Although adalimumab is effective in Crohn's disease, most patients experience a loss of response over time. The aim of the present study was to evaluate efficacy and safety of adalimumab dose escalation and identify predictors of a clinical response in Crohn's disease patients with a secondary loss of response. Methods: We performed a retrospective and observational study including all Crohn's disease patients who underwent dose escalation of adalimumab after a secondary loss of response from 2007 to 2015. Results: A clinical response was observed in 99/124 (79%) patients at 3 months and in 62/107 (61%) patients at 12 months. The predictive factors of response to ADA dose escalation at 12 months on multivariate analysis were: maintenance therapy of 40 mg every week rather than 80 mg every other week (OR 3.64, 95% CI: 1.28–10.37) and a CRP level ≤ 5 mg/L at adalimumab dose escalation (OR 6.64, 95% CI: 1.40–27.53). Adalimumab was withdrawn in 4 patients due to side effects. Conclusions: Adalimumab dose escalation is an effective and well-tolerated therapeutic option in patients with secondary loss of response. A 40 mg every week optimized regimen was predictive of a response to ADA dose escalation.